Exploring The Ecotourism Paradox: Perspective of Local Residents in Accredited Ecotourism Sites in Laguna Province Towards Sustainable Ecotourism Development - Ruiz, Merlu U (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
Ecotourism is a form of travel which has a potential to serve as an environmentally, socioculturally, and economically viable option for promoting sustainable tourism development. Whilst ecotourism can be a financially rewarding activity for the local economy, it can also have some drawbacks, just like any other kind of tourism, that must be addressed. The study aimed to explore the paradox on accredited ecotourism sites manifested in the province of Laguna. The study significantly concluded education paradox - as a means to promote sustainable practices may have a downside, as ecotourism sites failed to offer educational activities and the location paradox- the conflicting views on sustainable ecotourism among different demographics pose challenges for achieving genuine sustainability of on ecotourism. The significant differences in perceptions across locations reveal a tension. These paradoxes highlight the complexities of achieving truly sustainable ecotourism. Addressing them requires a holistic approach that acknowledges trade-offs, embraces diverse perspectives, and prioritizes long-term well-being over short-term gains.